Validitas Rantai Periwayatan Hadis di Era Digital: Analisis Otentisitas melalui Pendekatan Digital Isnād Mapping - Rendi Syahrinal Harahap (Yayasan Albahriah Jamiah Indonesia, 2025)
The validity of the sanad (chain of transmission) is a fundamental aspect in hadith studies because it determines the level of authenticity of a narration as a source of Islamic teachings. However, in the digital era, the complexity of narration data and the proliferation of online information pose new challenges in the process of verifying sanad accurately and systematically. This study aims to analyze the authenticity of hadith through a digital isna d mapping approach, a method of mapping the chain of transmission that integrates the principles of classical sanad criticism with relational data-based digital technology. Using a qualitative-descriptive approach and comparative analysis, this study examines several sanad datasets from various digital collections to identify transmission patterns, narrator relationships, and weak points in the chain of transmission. The results show that digital isna d mapping is able to more transparently reveal the structure of the narrator network, detect transmission anomalies, and verify the consistency of relationships between narrators with a high degree of accuracy. The application of this method not only strengthens the methodological dimension in sanad criticism but also presents a technology-based verification model that is efficient, accountable, and compatible with the needs of contemporary hadith studies. In conclusion, this research makes a significant contribution to the revitalization of the epistemology of hadith science through the integration of digital technology in the analysis of the authenticity of sanad, while also opening a new direction for the development of hadith criticism methodology in the digital era.